Trends and relationship between antimicrobial resistance and antibiotic use in Xinjiang Uyghur Autonomous Region, China: Based on a 3 year surveillance data, 2014-2016 - Haishaerjiang Wushouer; Zhao-Xia Zhang; Jian-Hua Wang; Ping Ji; Qing-Fang Zhu; Renagu Aishan; Lu-Wen Shi (Elsevier, 2018)
Purposes: The objective of the study was to identify the trends and relations between antimicrobial resistance (AMR) and antibiotic use in the Xinjiang Uyghur Autonomous Region in Western China from 2014 to 2016. Methods: A retrospective, descriptive analysis of AMR prevalence, and trends and relations between AMR and antibiotic use during the 3-year period was performed. Results: Third-generation cephalosporin-resistant Escherichia coli was the most prevalent resistant pathogen in terms of both resistance density and resistance proportion. A significant correlation was found between resistance density of third-generation cephalosporin-resistant Klebsiella pneumoniae and the use of beta-lactam-beta-lactamase inhibitor combinations (cc = 0.63, p = 0.03), quinolones (cc = 0.60, p = 0.04), and carbapenems (cc = 0.76, p = 0.004), among which only beta-lactam-beta-lactamase inhibitor combinations showed a significant correlation with third-generation cephalosporin-resistant E. coli (cc = 0.63, p = 0.03). For carbapenem-resistant Pseudomonas aeruginosa, not only carbapenem use (cc = 0.65, p = 0.02) but also penicillin (cc = 0.76, p = 0.004) and quinolone (cc = 0.69, p = 0.01) use showed significant correlation. A strong correlation was observed between the resistant proportion of third-generation cephalosporin-resistant E. coli and only the use of beta-lactam-beta-lactamase inhibitor combinations (cc = 0.61, p = 0.03). Conclusion: The association between antibiotic use and AMR, especially the implication of the difference in resistance density and resistance proportion, is crucial for local physicians and decision-makers to better use of antibiotics and allocate healthcare resources more effectively, as well as to better implement antimicrobial stewardship and effective infection control strategies. Keywords: Relation, Antimicrobial resistance, Antibiotic use, Prevalence